Whole-brain connectivity during encoding: age-related differences and associations with cognitive and brain structural decline. (22nd February 2022) - Capogna, Elettra; Sneve, Markus H; Raud, Liisa; Folvik, Line; Ness, Hedda T; Walhovd, Kristine B; Fjell, Anders M; Vidal-Piñeiro, Didac
Abstract: There is a limited understanding of age differences in functional connectivity during memory encoding. In the present study, a sample of cognitively healthy adult participants ( n  = 488, 18–81 years), a subsample of whom had longitudinal cognitive and brain structural data spanning on average 8 years back, underwent functional magnetic resonance imaging while performing an associative memory encoding task. We investigated (1) age-related differences in whole-brain connectivity during memory encoding; (2) whether encoding connectivity patterns overlapped with the activity signatures of specific cognitive processes, and (3) whether connectivity associated with memory encoding related to longitudinal brain structural and cognitive changes. Age was associated with lower intranetwork connectivity among cortical networks and higher internetwork connectivity between networks supporting higher level cognitive functions and unimodal and attentional areas during encoding. Task-connectivity between mediotemporal and posterior parietal regions—which overlapped with areas involved in mental imagery—was related to better memory performance only in older age. The connectivity patterns supporting memory performance in older age reflected preservation of thickness of the medial temporal cortex. The results are more in accordance with a maintenance rather than a compensation account.